Pengaruh Penglelupasan Honeycomb sandwich Terhadap Perilaku Perambatan retak Lelah Al 2024 T3 - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Perikanan Fak. Pertanian UGM, 2003)
The effect of the peelness honeycomb sandwich on the characteristic of fatigue crack growth rate of aluminium alloy Al 2024-T3 has been investigated. Firstly, the test was carried out under sinusoidal loads with constant amplitude at the stress ratio (R) of 0,3. Secondly, the process is the same with the previous one but it was followed by a single tension overload with the overload ratio (OLR) of 1,5 and 2,0. Application of the overload was conducted manually at a static load 'after the crack propagated approximately 4,0 mm length. The experimental results show that, in the fatigue crack growth rate, the pee/ness honeycomb sandwich is slightly better than the base material. The existense of a single overload ratio can decrease the crack growth rate. The effect of the stress ratio can decrease the crack growth rate for getting higher stress ratio.